Formulation Design and Characterization of Transdermal Films of Amlodipine Besylate for Enhancing Therapeutic Efficacy - Sharmin, Tusnova; Rashid, Mamun; Uddin, Giash; Hossain, Mohammad; Arefin, Sayema; Hossain, Monir (Jordan Journal of Pharmaceutical Sciences, 2020)
This study is designed to develop Hydroxypropyl Methylcellulose (HPMC) based polymeric films of amlodipine besylate to explore HPMC as a rate retardant polymer in transdermal drug delivery system. Films were formulated by the solvent casting method. Physicochemical parameters of the films were evaluated (film permeability, elongation, pH, drug content uniformity and release kinetics). Results found that the elongation of formulated films were about 3.33-13.33%, whereas surface pH varies from 6.82 to 6.97. Maximum permeability flux was found 0.384 gm cm-2/day for ABF7; whereas minimum for ABF3 (0.338 gm cm-2/day). After 8 hours, the highest release (95.77%) was for ABF6; whereas 83.67% (least) release was for ABF3 and ABF5. For dissolution patterns, among different kinetic models, the Higuchi model was fitted nicely for release kinetic of the formulated films. It revealed that the drug release pattern and kinetics were affected due to the change in the polymer-drug ratio and solvents. It showed that HPMC plays a significant role in dissolution rate. In conclusion: we found that ABF7 is the best fit formulation for preparing HPMC based transdermal film of amlodipine besylate. Further investigation is warranted to correlate in-vitro and in-vivo findings for the potential therapeutic use.